Science play in the verbatim theatre: God and Newton's religious worldview in Craig Baxter's Play Let Newton Be! (2011) - Alenkina, Tatiana B. (Имагология и компаративистика)
The article is aimed at analyzing the representation of the image of Isaac Newton in the genre of the science play. The hermeneutic analysis contributes to the unfolding of the image in the transformative way; Isaac Newton tells the story of his life, success, and science interests through numerous sources, presenting himself not as a hero of science but as a man in the whole complexity of his controversial personality. The problem of selecting the sources and the use of artistic expressive means helps us better see the secret life of Newton and brings us back to the problem of a science play as a genre.